(untitled) (Indian Journal of Arid Horticulture, 2025)
A pot experiment on Bael (Aegle marmelos Correa) seedlings was conducted during September 2005 to May 2006 in completely randomized design with three replications and nine treatments of each element at the Department of Horticulture, Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, Udham Singh Nagar, Uttarakhand. Nine different treatments of nitrogen and phosphorus each were applied in the experiment. Results of the present investigation revealed that nitrogen and phosphorus deficiency resulted in reduced vegetative growth attributes of bael seedling. In nitrogen deficiency maximum height of seedling (13.67 cm), number of leaves (15.00), length of leaf (11.20 cm), breadth of leaf (3.23 cm) were found with T, (control) and total chlorophyll content (1.814 mg/g fresh weight) was found with T. While minimum values were obtained with T, (without nitrogen). In the present results, the critical level of nitrogen was considered as 0.65 per cent on dry weight basis.